2002
DOI: 10.1152/ajpheart.00038.2002
|View full text |Cite
|
Sign up to set email alerts
|

Conduction of hyperpolarization along hamster feed arteries: augmentation by acetylcholine

Abstract: The conduction of vasodilation along resistance vessels has been presumed to reflect the electrotonic spread of hyperpolarization from cell to cell along the vessel wall through gap junction channels. However, the vasomotor response to acetylcholine (ACh) encompasses greater distances than can be explained by passive decay. To investigate the underlying mechanism for this behavior, we tested the hypothesis that ACh augments the conduction of hyperpolarization. Feed arteries (n = 23; diameter, 58 +/- 4 microm; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 32 publications
13
125
0
Order By: Relevance
“…8,9 Conduction velocity has been estimated to 41 to 3 mm/s in intracellular Ca 2 þ or diameter measurements with limited time-resolution [10][11][12][13] and 420 to B45 mm/s in electrophysiological recordings with higher time-resolution. 14,15 For comparison, the velocity of intercellular Ca 2 þ waves spreading along arterioles has been estimated toB0.1 mm/s. 16,17 Thus, conducted vasomotor responses spread with velocities that are 1 to 3 orders of magnitude faster than the spread of intercellular Ca 2 þ waves.…”
Section: Definition Of Vascular Conducted Responsementioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Conduction velocity has been estimated to 41 to 3 mm/s in intracellular Ca 2 þ or diameter measurements with limited time-resolution [10][11][12][13] and 420 to B45 mm/s in electrophysiological recordings with higher time-resolution. 14,15 For comparison, the velocity of intercellular Ca 2 þ waves spreading along arterioles has been estimated toB0.1 mm/s. 16,17 Thus, conducted vasomotor responses spread with velocities that are 1 to 3 orders of magnitude faster than the spread of intercellular Ca 2 þ waves.…”
Section: Definition Of Vascular Conducted Responsementioning
confidence: 99%
“…This has led to the hypothesis that a regenerative mechanism exist in the vascular wall, which would account for propagation of a hyper-or depolarization over long distances in the microcirculation. 15,26,35,53 In hamster retractor muscle feed arteries, it was shown that inward-rectifier (K IR ) K þ channels possess the inherent biophysical properties necessary to facilitate the conducted hyperpolarization and vasodilatation to local ACh application. Using a range of in vitro methods and computational modeling, it was shown that the negative-slope conductance of K IR channels during hyperpolarization of VSMCs would augment the initial hyperpolarization as it conducts through VSMCs along the vascular wall.…”
Section: How Vascular Conducted Responses Are Typically Measuredmentioning
confidence: 99%
“…13,57 This can occur bidirectionally along the length of the vessel, and is intrinsic to the wall of the artery, relies on the endothelium, and is not dependent on either nerves or blood flow change. 13,54,[58][59][60][61] The phenomenon is well-characterized within the microcirculation, where studies in exteriorized vascular beds in situ, 55 and arterioles isolated from those vascular beds, have used the endothelium-dependent agonist ACh to evoke robust responses when applied to the outside of arterioles with micropipettes. Spreading dilatation can also be sustained in small resistance arteries, such as the rat mesenteric artery, which have 3-5 layers of muscle, illustrating its relevance across the vasculature.…”
Section: Conducted Hyperpolarizationmentioning
confidence: 99%
“…Simulations demonstrate that the cable length constant, λ el , is inversely proportional to the square root However, a value of 3.3 MΩ was estimated by Lidington et al [155] for rat skeletal muscle. Based on this value, the predicted λ el was in close agreement with the experimental λ el value determined in guinea-pig small intestine arterioles [146], hamster feed arteries [164], and with dilatation data from RMA [81,133]. After disruption of the endothelial gap junctions, the ability of the model vessel to carry spreading responses was minimized as indicated by a large decrease in λ el ( [135] and in [123].…”
Section: Role Of Gap Junctions In V M Spreadsupporting
confidence: 80%
“…In hamster feed arteries, the conduction of hyperpolarization was augmented during Ach stimulation compared to electric current stimulation [164]. This augmentation was indicated by an increase in the length constant from λ el = 1.2 mm to λ el,Ach = 1.9 mm.…”
Section: Role Of Endothelial Cell Ca 2+ Spreadmentioning
confidence: 89%